Maternal Immunization: Nature Meets Nurture - Saso, Anja; Kampmann, Beate (Frontiers in Microbiology, 2020)
Vaccinating women in pregnancy (i.e. maternal immunisation) has emerged as a promising tool to tackle infant morbidity and mortality worldwide. This approach nurtures a ‘gift of nature,’ whereby antibody is transferred from mother to fetus transplacentally during pregnancy, or postnatally in breast milk, thereby providing passive, antigen-specific protection against infections in the first few months of life, a period of increased immune vulnerability for the infant. In this review, we briefly summarise the rationale for maternal immunisation programmes and the landscape of vaccines currently in use or in the pipeline. We then direct the focus to the underlying biological phenomena, including the main mechanisms by which maternally-derived antibody is transferred efficiently to the infant, at the placental interface or in breast milk; important research models and methodological approaches to interrogate these processes, particularly in the context of recent advances in systems vaccinology; the potential biological and clinical impact of high maternal antibody titres on neonatal ontogeny and subsequent infant vaccine responses; and key vaccine- and host-related factors influencing the maternal-infant dyad across different environments. Finally, we outline important gaps in knowledge and suggest future avenues of research on this topic, proposing potential strategies to ensure optimal testing, delivery and implementation of maternal vaccination programmes worldwide.